ETHICS AND LAW ON FLAMING ON YOUTUBE: A PERCEPTION FROM THE FLAMERS ON YOUTUBE - Norizah Aripin; Sabrina Mohd Rashid; Awan Ismail; Revathy Amadera Limgam (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Flaming activity on YouTube is a part of cyber-bullying in social media. Today, the YouTube website has been labelled as a page that contains a lot of flaming. It is claimed that flamers debate and comment on the issues on YouTube without taking ethics and law into consideration. The design of this research is to study the views and opinions on law and ethics in the use of YouTube from the flamer’s point of view. This study uses a qualitative methodology. Face-to-face interviews are conducted by involving five informants who are the flamers on YouTube. Thematic analysis is used to analyse the data. The findings show that informants have an understanding of certain ethics before flaming on YouTube. However, almost all the informants have a lack of knowledge of the laws implemented on cybersecurity in Malaysia especially on flaming on YouTube. The findings of this study conclude that informants practice a certain type of ethics when accessing YouTube, but lack awareness of the laws implemented on cybersecurity when commenting on the site.